2018
DOI: 10.1002/alr.22090
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of the medial wall of the prelacrimal recess

Abstract: The anteroposterior and superoinferior dimensions of the medial wall of the PLR are variable, with the anteroposterior dimension being widest inferiorly. Its dimensions should be evaluated preoperatively when considering endoscopic approaches to or through the anterior maxillary sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
(17 reference statements)
0
15
0
1
Order By: Relevance
“…Thus, EPLAs may save more time than MMAs without additional complications, especially when treating cases in which inflammatory polyps full of maxillary sinus. In these cases, stripping lesions arising from the anterior and/or medial aspect of maxillary sinus (e.g., alveolar or PLR) present an obstacle for standard MMA approach (Turri-Zanoni et al, 2017;Kashlan & Craig, 2018). Nonetheless, further studies are needed to elucidate whether patients with inflammatory maxillary disease undergoing EPLAs have results comparable with those treated with conventional MMAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, EPLAs may save more time than MMAs without additional complications, especially when treating cases in which inflammatory polyps full of maxillary sinus. In these cases, stripping lesions arising from the anterior and/or medial aspect of maxillary sinus (e.g., alveolar or PLR) present an obstacle for standard MMA approach (Turri-Zanoni et al, 2017;Kashlan & Craig, 2018). Nonetheless, further studies are needed to elucidate whether patients with inflammatory maxillary disease undergoing EPLAs have results comparable with those treated with conventional MMAs.…”
Section: Discussionmentioning
confidence: 99%
“…Antero-posterior (AP) diameter was first defined as the distance from pyriform aperture to the nasolacrimal duct (NLD) by identifying the inferior-most aspect of NLD on coronal view and then transposing that to axial view. The height of medial PLR was measured starting at the level of the superior-most aspect of the NLD to the nasal floor, as described in Kashlan & Craig (2018). Other demographic data including age, gender, initial symptoms and their durations, image findings and known surgical history of each patient were also collected from each patient prior to surgery.…”
Section: Study Design and Patient Eligibilitymentioning
confidence: 99%
“…The anteroposterior and superoinferior dimensions of the medial wall of the prelacrimal recess vary, 19,20 and we should evaluate its dimensions preoperatively in order to avoid the NLD injury. Our previous and other studies reported that NLD is preserved in the PLRA, 9,10,12,1416 a finding that was echoed in our results of the present study as well.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the distance between the pyriform aperture and nasolacrimal duct is variable and most cases require skeletonizing of the lacrimal system before entering the maxillary sinus anterolateral to it . The need to skeletonize the lacrimal system allows it to be mobilized together with the inferior turbinate flap but also provides access for the management of lacrimal system pathology; the senior author has utilized the prelacrimal recess technique in the resection of juvenile nasopharyngeal angiofibroma and lacrimal tumors which has previously been reported by other surgical teams .…”
Section: Discussionmentioning
confidence: 99%